Exploring the Physicochemical Properties of Moringa oleifera Leaf Powder from Lampung Selatan, Indonesia: Eksplorasi Karakteristik Fisiko-Kimia Bubuk Daun Kelor Asal Lampung Selatan, Indonesia - Witoyo, Jatmiko Eko; Afifah, Amalia; Saraswati, Ayu Rahayu; Ristianti, Wigi Putri; Sari, Yanti (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
Moringa oleifera leaves (MOL) are one of the food ingredients that have complete nutritional content at an affordable price. These leaves are found in several regions of Indonesia, including Lampung Selatan. However, a notable drawback of MOL is its limited shelf life, and it is commonly transformed into Moringa oleifera leaf powder (MOLP) to enhance longevity. This study aims to explore the physicochemical properties of MOLP from Lampung Selatan, which has not been widely examined. This approach used in this study was quantitative descriptive. The results showed that the MOLP from Lampung Selatan had showed  L* value of 59.36, a* value of -8.05, and b* value of 23.36. It additionally revealed 21.10% protein, 3.49% fat content, 0.73% ash content, 5.83% moisture content, 68.84% carbohydrate content, 6.87% crude fiber content, and 15.47% starch. These results indicate that the MOLP from Lampung Selatan had a green colour, high in protein and crude fiber content, and low in fat and starch content. Therefore, MOLP from Lampung Selatan exhibits encouraging potential as a functional food ingredient in the development of food products requiring a high protein and fiber content at an affordable price.